An examination of mechanical properties of dissimilar AISI 304 stainless steel and copper weldment obtained using GTAW. (2020) - Singh, Gurdeep; Saxena, Ravindra K.; Pandey, Sunil
Abstract: In this study of examination, the mechanical properties of AISI 304 stainless steel and copper fabricated by gas tungsten arc welding process (GTAW) are evaluated. Dissimilar material welding of AISI 304 stainless steel and copper are chosen in the industry because of their high tensile strength, hardness, good corrosion resistance and high electrical or thermal conductivity. The copper is difficult to welding because of high thermal conductivity which in turn tends to dissipate heat rapidly away from the weld leading to difficulties in reaching the melting temperature. In addition, high thermal expansion meaning that distortion can occur during welding. Due to the differences in material properties, there is uneven partitioning of the heat at the joint interface in dissimilar welding. To compensate for heat loss at the interface between these weld pads the heat source or welding torch was traversed at an off-setting distance toward copper. The purpose of this study is to evaluate the mechanical properties of the dissimilar weldment using gas tungsten arc welding (GTAW) for AISI 304 SS and copper with 1.25 mm offsetting distance. To reveal the effectiveness of the proposed scheme the mechanical properties in terms of micro-hardness and tensile strength of weldment are evaluated for the weldment viz-a-viz copper.